Black Money Usage Tracker Mechanism Based on Hyperledger Fabric - Abdukodirov, Farkhod; Kim, Ki Hyung (Journal of Korean Institute of Communications and Information Sciences, 2020)
Black money and fake money are two major conundrums to the development of the third world and particularly less economically developed countries worldwide. In the paper, we propose the mechanism which records money exchange information including the particular money with serial number, date, owner on the ledger and informs about black money when serial number does not match with the Public Ledger information.
Keywords: Blockchain; Chaincode; Golang; Hyperledger Fabric; Node.js; QR code; Smart Contract; Transaction; Web API